A two-dimensional MXene-based active electrode material, preparation method and artificial synaptic device
By using sulfur-modified two-dimensional MXene-based active electrode material in synaptic devices and interpolated one-dimensional nanomaterials, the problems of insufficient dynamic range and poor linearity of existing synaptic devices are solved, and synaptic devices with high dynamic range and good linearity are achieved, which are suitable for the needs of neuromorphic systems.
Patent Information
- Application Number
- CN202411065979.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-05
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-08-05
AI Technical Summary
Existing synaptic devices have problems such as insufficient dynamic range and poor linearity, which cannot meet the needs of neuromorphic systems.
A two-dimensional MXene-based active electrode material is used to increase the active site through sulfur modification, and a one-dimensional nanomaterial is interposed in the two-dimensional MXene to regulate the electron and ion transport characteristics of the material.
It improves the dynamic range and linearity of synaptic devices, reduces energy consumption, enhances conductivity, and is suitable for large-scale production.
Smart Images

Figure CN119160893B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of active electrode materials, and specifically relates to a two-dimensional MXene-based active electrode material, a preparation method and an artificial synaptic device. Background Art
[0002] With the rapid development of fields such as artificial intelligence, the Internet of Things, and machine learning, the traditional von Neumann architecture can no longer cope with the growing demand for data processing. The emerging brain-inspired neuromorphic computing system is seen as a potential solution to break through the bottleneck of the von Neumann architecture. Artificial synapses are used to imitate neural transmission and physical information perception and are an important structure of neuromorphic systems. However, existing synaptic devices have problems such as insufficient dynamic range and poor linearity, which cannot meet the needs of neuromorphic systems. It is urgent to develop synaptic devices with high dynamic range and good linearity.
[0003] Redox synapses are an important type of artificial synaptic devices, and their structure is roughly top electrode / electrolyte layer / resistance change layer / bottom electrode. They achieve the resistance change of synapses through redox reactions at both ends of the device. As part of the device, the electrode material has a decisive influence on the redox reaction of the device. However, existing research has rarely studied the electrode materials of synapses. For this reason, it is of great significance to develop new redox synaptic active materials. Summary of the invention
[0004] In order to overcome the problems existing in the prior art, the present invention provides a two-dimensional MXene-based active electrode material, a preparation method and an artificial synaptic device.
[0005] A method for preparing a two-dimensional MXene-based active material comprises the following steps:
[0006] S1. Prepare two-dimensional MXene nanosheet dispersion using MXene precursor MAX phase;
[0007] S2. In situ growing sulfur particles on the two-dimensional MXene nanosheet dispersion to prepare a sulfurized MXene nanosheet dispersion;
[0008] S3. Insert one-dimensional nanomaterials into the sulfide MXene nanosheet dispersion to obtain two-dimensional MXene-based active materials after treatment.
[0009] According to the aspects and any possible implementation methods described above, an implementation method is further provided, wherein S1 specifically includes: under the action of a mixed liquid of HCl and LiF, the MXene precursor MAX phase is wet-etched into a two-dimensional MXene nanosheet at a first set temperature, and reacts for a certain time; a multilayer MXene dispersion is prepared by acid washing, water washing and centrifugation; and a few-layer MXene dispersion is further obtained by ultrasonic stripping.
[0010] According to the above aspects and any possible implementation, there is further provided an implementation, wherein the first set temperature is 30° C.-90° C., and the certain time is 24 h-120 h.
[0011] According to the aspects and any possible implementation methods described above, an implementation method is further provided, wherein S2 specifically includes: utilizing S element to react with Na2S·9H2O at a second set temperature to generate a Na2S4 solution, mixing the Na2S4 solution with a few-layer MXene solution, and causing sodium polysulfide to undergo a disproportionation reaction under the action of formic acid to load micron-sized sulfur element on the MXene, and further obtaining a sulfide MXene nanosheet dispersion by centrifugation and washing with water.
[0012] According to the above aspects and any possible implementation, there is further provided an implementation, wherein the second set temperature is 30° C.-50° C., and the corresponding insulation time is 3 h-6 h.
[0013] According to the aspects and any possible implementation methods described above, an implementation method is further provided, wherein S3 specifically comprises stirring and mixing the sulfide MXene nanosheet dispersion and the one-dimensional nanomaterial at room temperature for more than 24 hours, and then ultrasonically treating for 15 minutes to obtain a two-dimensional MXene-based active electrode material.
[0014] According to the above aspects and any possible implementation manner, an implementation manner is further provided, wherein the one-dimensional nanomaterial includes single-walled carbon nanotubes, multi-walled carbon nanotubes, metal nanowires and / or carbon fibers.
[0015] The present invention also provides a two-dimensional MXene-based active electrode material, which is obtained by using the preparation method.
[0016] The present invention also provides an artificial synaptic device, which includes a top electrode layer, an ion electrolyte layer, a resistive switching layer and a bottom electrode layer, wherein the top electrode layer adopts the two-dimensional MXene-based active electrode material.
[0017] According to the above aspects and any possible implementation, an implementation is further provided, wherein the ionic electrolyte layer is a polyurethane-based lithium salt, the resistive switching layer is a reduced PEDOT:PSS, and the bottom electrode layer is ITO.
[0018] Beneficial effects of the present invention
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1) The present invention increases the active sites of two-dimensional MXene-based materials through sulfur modification, increases the reaction probability of lithium ions and MXene, and improves the dynamic range of synaptic devices.
[0021] 2) The present invention regulates the interlayer spacing of two-dimensional MXene through the intercalation of one-dimensional materials in two-dimensional MXene, improves the transport properties of electrons and ions, and thereby changes the relevant performance indicators of the synapse, such as energy consumption and linearity.
[0022] 3) The preparation method proposed in the present invention is simple, easy to implement, low-cost, and highly scalable. The required materials are inexpensive and do not require complex processing equipment, making it suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a scanning electron microscope (SEM) image of the two-dimensional MXene material in Preparation Example 1;
[0024] Figure 2 This is the transmission electron microscope TEM image of the S@MXene material in Preparation Example 1;
[0025] Figure 3a , 3b , 3c and 3d are the SEM images of the two-dimensional MXene film in Preparation Example 2 and the EDS spectrum analysis of sulfur, titanium and carbon elements, respectively;
[0026] Figure 4 It is the XRD spectrum of MXene, S@MXene, and S@MXene after one-dimensional material intercalation in Preparation Example 2;
[0027] Figure 5 is the voltage pulse characteristic curve of the artificial synaptic device in Preparation Example 3;
[0028] Figure 6 is the voltage pulse characteristic curve of the artificial synaptic device in Preparation Example 4;
[0029] Figure 7 The voltage pulse characteristic curve of the artificial synaptic device in Preparation Example 5;
[0030] Figure 8 It is a schematic diagram of the method flow of the present invention. DETAILED DESCRIPTION
[0031] In order to better understand the technical solution of the present invention, the content of the present invention includes but is not limited to the specific implementation methods described below, and similar technologies and methods should be considered to be within the scope of protection of the present invention. In order to make the technical problems, technical solutions and advantages to be solved by the present invention clearer, the following will be described in detail with reference to the accompanying drawings and specific embodiments.
[0032] It should be clear that the embodiments described in the present invention are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0034] like Figure 8 As shown, the present invention provides a method for preparing a two-dimensional MXene-based active material, comprising the following steps:
[0035] S1. Prepare two-dimensional MXene nanosheet dispersion using MXene precursor MAX phase;
[0036] S2. In situ growing sulfur particles on the two-dimensional MXene nanosheet dispersion to prepare a sulfurized MXene nanosheet dispersion;
[0037] S3. Insert one-dimensional nanomaterials into the sulfide MXene nanosheet dispersion to obtain two-dimensional MXene-based active materials after treatment.
[0038] Specifically, the specific process of the present invention is as follows:
[0039] (1) Under the action of a mixed liquid of HCl and LiF, the precursor MAX phase is etched into two-dimensional MXene nanosheets by wet etching at a first set temperature and reacted for a certain period of time. Since the wet etching method has a higher yield and the etched two-dimensional material has a better quality, the present invention adopts this method. A multilayer MXene dispersion is prepared by acid washing, water washing and centrifugation; further, ultrasonic stripping is performed to obtain a few-layer MXene dispersion from the multilayer MXene dispersion. The few-layer MXene has a larger specific surface area, which is beneficial to the subsequent sulfurization step;
[0040] (2) Using S element and Na2S·9H2O to react at the second set temperature in a deionized water system to generate Na2S4 solution, which is mixed with an appropriate amount of a few-layer MXene aqueous solution. Under the action of a magnetic stirrer, formic acid is gradually added to the mixed solution. Under the action of formic acid, sodium polysulfide undergoes a disproportionation reaction to uniformly load micron-sized sulfur element on MXene. Further centrifugation and water washing can obtain sulfurized MXene, which is recorded as S@MXene. The loaded sulfur particles serve as active sites, increasing the reaction probability of lithium ions and active electrodes. In addition, in this step, different concentrations of MXene dispersions are added to adjust the sulfur content loaded on MXene. The obtained S@MXene dispersion is stirred and mixed with the one-dimensional nanomaterial at room temperature for more than 24 hours, and then ultrasonically treated for 15 minutes to obtain a two-dimensional MXene-based active electrode material. In this step, the one-dimensional nanomaterial changes the transport path of electrons and ions between the two-dimensional MXene layers through the intercalation effect between the two-dimensional MXene layers, and finally prepares synaptic electrode materials with different characteristics. The electrodes after intercalation of one-dimensional nanomaterials reduce the energy consumption of synaptic devices, improve the linearity of the devices, and transform the conductivity enhancement and inhibition characteristics of synaptic devices, thus enriching the application range of the devices. Furthermore, by adjusting the relative content of one-dimensional nanomaterials and S@MXene dispersion, synaptic electrode materials with different characteristics can be obtained.
[0041] The above preparation method is further configured as follows: the first set temperature is 30°C-90°C.
[0042] The above preparation method is further configured such that the reaction time at the first set temperature is 24h-120h.
[0043] Preferably, the surface of the prepared two-dimensional MXene-based active electrode material is uniformly modified with micron-sized sulfur particles.
[0044] Preferably, two-dimensional MXene can be regulated by one-dimensional nanomaterials to obtain MXene materials with different synaptic properties.
[0045] Preferably, the MAX phase in step (1) can be Ti3AlC2, V2AlC, Nb2AlC or Ti2AlC, all of which are precursor phases of MXene.
[0046] Preferably, MXene can be Ti3C2, V2C, Nb2C or Ti2C, all of which belong to the category of two-dimensional MXene materials.
[0047] Preferably, the one-dimensional nanomaterial includes single-walled carbon nanotubes, multi-walled carbon nanotubes, metal nanowires and / or carbon fibers.
[0048] Preferably, the preparation process of the MXene active material is carried out in a deionized water system.
[0049] Preferably, the properties of the MXene active electrode material can be regulated by the content of loaded sulfur.
[0050] Preferably, the performance of the MXene active electrode material can be regulated by the intercalation content of CNTs.
[0051] As an embodiment disclosed by the present invention, the present invention also provides a two-dimensional MXene-based active electrode material, which is obtained by the preparation method. The two-dimensional MXene-based active electrode material has abundant sulfur active sites. Under the action of pulse voltage, it can regulate synaptic conductance through electrochemical doping after reacting with lithium ions, thereby realizing the function of artificial synapse.
[0052] As an embodiment disclosed in the present invention, the present invention also provides an artificial synaptic device, the device includes a top electrode layer, an ion electrolyte layer, a resistive switching layer and a bottom electrode layer, the top electrode layer adopts the two-dimensional MXene-based active electrode material of the present invention; the ion electrolyte layer is a polyurethane-based lithium salt, the resistive switching layer is a blend of reduced poly(3,4-ethylenedioxythiophene) and polystyrene sulfonate (PEDOT:PSS), and the bottom electrode layer is indium tin oxide (ITO). Some embodiments are used to illustrate:
[0053] Preparation Example 1
[0054] Follow the steps below:
[0055] The precursor MAX phase material Ti3AlC2, LiF, and HCl were mixed in a reactor at a molar ratio of 1:24:72, and reacted at 40°C and 400 rpm for 48 hours. After acid washing, water washing, and centrifugation, the supernatant after centrifugation was black and had a pH value of 7. The centrifugation parameters were 3500 rpm and the time was 10 minutes. The MXene system was further ultrasonically exfoliated under the protection of argon for 30 minutes. Finally, under the centrifugation at 3500 rpm and 30 minutes, a few-layer Ti3C2T x The concentration of the dispersion is about 10 mg / ml.
[0056] Na2S·9H2O and elemental S powder were mixed in a molar ratio of 1:3 and stirred at 40°C for 3 h on a magnetic stirrer to generate a Na2S4 solution, which was a light yellow liquid. x The dispersion was mixed and stirred for 30 min, and 0.1 mol / L HCOOH was added to cause the Na2S4 solution to undergo a disproportionation reaction.x Micron-sized sulfur is generated on the surface. After further washing and centrifugation, 80% of the supernatant is poured off to obtain sulfided Ti3C2T x Dispersion, denoted as S@Ti3C2T x . Figure 1 For the preparation of Ti3C2T x SEM image of the nanosheet. As can be seen from the figure, two-dimensional Ti3C2T was successfully etched. x Material; Figure 2 S@Ti3C2T x In the TEM image, we can see that the protruding black part is sulfur particles, which are about 2μm in size. Figure 3a , 3b , 3c and 3d are S@Ti3C2T x The SEM image of the film and the EDS elemental analysis results show that the sulfur particles are evenly distributed in the Ti3C2T x On a two-dimensional material as a substrate.
[0057] Preparation Example 2
[0058] The precursor MAX phase material Ti3AlC2, LiF, and HCl were mixed in a reactor at a molar ratio of 1:24:72, and reacted at 40°C and 400 rpm for 48 hours. After acid washing, water washing, and centrifugation, the supernatant after centrifugation was black and had a pH value of 7. The centrifugation parameters were 3500 rpm and the time was 10 minutes. The MXene system was further ultrasonically exfoliated under the protection of argon for 30 minutes. Finally, under the centrifugation at 3500 rpm and 30 minutes, a few-layer Ti3C2T x The concentration of the dispersion is about 10 mg / ml.
[0059] Na2S·9H2O and elemental S powder were mixed in a molar ratio of 1:3 and stirred at 40°C for 3 h on a magnetic stirrer to generate a Na2S4 solution, which was a light yellow liquid. x The dispersion was mixed and stirred for 30 min, and 0.1 mol HCOOH was added to cause the Na2S4 solution to undergo a disproportionation reaction. x Micron-sized sulfur is generated on the surface. After further washing and centrifugation, 80% of the supernatant is poured off to obtain sulfided Ti3C2T x Dispersion, denoted as S@Ti3C2T x ; Further, S@Ti3C2T x The dispersion was mixed with single-walled carbon nanotubes (SWNTS) and stirred for 24 h, and then ultrasonicated for 15 min to obtain S@Ti3C2T x- SWNTS active material dispersion. Figure 4 Shown S@Ti3C2T after CNT intercalation x A cross-sectional view of Figure 5 The XRD patterns show that after CNT intercalation, the two-dimensional Ti3C2T x The interlayer spacing is significantly enlarged, which regulates the migration path of ions and further reduces the conductivity of the synaptic electrode material.
[0060] Preparation Example 3
[0061] The precursor MAX phase material Ti3AlC2, LiF, and HCl were mixed in a reactor at a molar ratio of 1:24:72, and reacted at 40°C and 400 rpm for 48 hours. After acid washing, water washing, and centrifugation, the supernatant after centrifugation was black and had a pH value of 7. The centrifugation parameters were 3500 rpm and the time was 10 minutes. The MXene system was further ultrasonically exfoliated under the protection of argon for 30 minutes. Finally, under the centrifugation at 3500 rpm and 30 minutes, a few-layer Ti3C2T x The concentration of the dispersion is about 10 mg / ml.
[0062] Na2S·9H2O and elemental S powder were mixed in a molar ratio of 1:3 and stirred at 40°C for 3 h on a magnetic stirrer to generate a Na2S4 solution, which was a light yellow liquid. x The dispersion was mixed and stirred for 30 min, and 0.1 mol HCOOH was added to cause the Na2S4 solution to undergo a disproportionation reaction. x Micron-sized sulfur is generated on the surface. After further washing and centrifugation, 80% of the supernatant is poured off to obtain sulfided Ti3C2T x Dispersion, denoted as S@Ti3C2T x .
[0063] Furthermore, S@Ti3C2T x The dispersion was mixed with multi-walled carbon nanotubes (MWNTS) and stirred for 24 h, and then ultrasonicated for 15 min to obtain S@Ti3C2T x -MWNTS active material dispersion.
[0064] Preparation Example 4
[0065] Based on the final product S@Ti3C2T in Preparation Example 1 x The artificial synaptic device was prepared, and the specific process is as follows:
[0066] The artificial synaptic device was constructed by pouring the solution layer by layer and drying it, and the drying process was carried out in a vacuum drying oven at 40°C. The top electrode active layer was S@Ti3C2T prepared in Example 1. x The material is a polyurethane-based lithium salt in the electrolyte layer, the lithium salt is lithium bis(trifluoromethanesulfonyl imide), the resistive layer is reduced PEDOT:PSS, and the bottom electrode is ITO. The device exhibits an excellent dynamic range, showing the characteristics of positive pulse enhancement and negative pulse suppression. The enhancement range reaches 174%, and the suppression range reaches 374%.
[0067] Figure 6 S@Ti3C2T x A synaptic device with electrode materials that exhibits enhancement under positive voltage and inhibition under negative voltage.
[0068] Preparation Example 5
[0069] Based on the final product S@Ti3C2T in Preparation Example 2 x -SWNTS active materials were used to prepare artificial synaptic devices. The specific process is as follows:
[0070] The artificial synaptic device was constructed by pouring the solution layer by layer and drying it, and the drying process was carried out in a vacuum drying oven at 40°C. The top electrode active layer was S@Ti3C2T prepared in Example 1. x -SWNTS material, the electrolyte layer is a polyurethane-based lithium salt, the lithium salt is lithium bis(trifluoromethanesulfonyl imide), the resistive layer is reduced PEDOT:PSS, and the bottom electrode is ITO. x The design of the active electrode changes the voltage pulse curve characteristics of the synapse, making the synapse exhibit the characteristics of positive pulse inhibition and negative pulse enhancement, which broadens the scope of use of artificial synaptic devices.
[0071] Figure 7 S@Ti3C2T after single-walled CNT intercalation x The electrode material synaptic device exhibits the characteristics of inhibition under positive voltage and enhancement under negative voltage. In addition, the energy consumption of the synaptic electrode material device is lower than that of S@Ti3C2T x Further reduce.
[0072] The above description shows and describes several preferred embodiments of the present invention, but as mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a two-dimensional MXene-based active material, characterized in that: The two-dimensional MXene-based active material is used in an artificial synaptic device, comprising the following steps: S1. Prepare two-dimensional MXene nanosheet dispersion using MXene precursor MAX phase; S2. In situ growth of sulfur particles on the two-dimensional MXene nanosheet dispersion to prepare a sulfide MXene nanosheet dispersion; specifically comprising: using S element and Na2S·9H2O to react at a second set temperature to generate a Na2S4 solution, mixing the solution with a few-layer MXene solution, and causing sodium polysulfide to undergo a disproportionation reaction under the action of formic acid to load micrometer-sized sulfur element on the MXene, and further centrifuging and washing to obtain a sulfide MXene nanosheet dispersion; S3. Inserting one-dimensional nanomaterials into the sulfide MXene nanosheet dispersion to obtain a two-dimensional MXene-based active material after treatment, specifically comprising: stirring and mixing the sulfide MXene nanosheet dispersion and the one-dimensional nanomaterial at room temperature for more than 24 hours, and then ultrasonically treating for 15 minutes to obtain a two-dimensional MXene-based active electrode material, wherein the one-dimensional nanomaterial changes the transport path of electrons and ions between the two-dimensional MXene layers through the intercalation effect between the two-dimensional MXene layers.
2. The preparation method according to claim 1, characterized in that: The S1 specifically includes: under the action of HCl and LiF, the MXene precursor MAX phase is wet-etched into two-dimensional MXene nanosheets at a first set temperature and reacts for a certain time; a multilayer MXene dispersion is prepared by acid washing, water washing and centrifugation; and a few-layer MXene dispersion is further obtained by ultrasonic stripping.
3. The preparation method according to claim 2, characterized in that: The first set temperature is 30° C.-90° C., and the certain time is 24h-120h.
4. The preparation method according to claim 1, characterized in that: The second set temperature is 30°C-50°C, and the corresponding insulation time is 3h-6h.
5. The preparation method according to claim 1, characterized in that: The one-dimensional nanomaterials include single-walled carbon nanotubes, multi-walled carbon nanotubes, metal nanowires and / or carbon fibers.
6. A two-dimensional MXene-based active electrode material, characterized in that: The material is obtained by the preparation method according to any one of claims 1 to 5.
7. An artificial synaptic device, characterized in that: The device comprises a top electrode layer, an ionic electrolyte layer, a resistive switching layer and a bottom electrode layer, wherein the top electrode layer adopts the two-dimensional MXene-based active electrode material according to claim 6.
8. The artificial synaptic device according to claim 7, characterized in that: The ion electrolyte layer is polyurethane-based lithium salt, the resistive switching layer is a blend of reduced poly(3,4-ethylenedioxythiophene) and polystyrene sulfonate PEDOT:PSS, and the bottom electrode layer is indium tin oxide ITO.
Citation Information
Patent Citations
Two-dimensional transition metal carbide (nitride) and nano sulfur particulate composite as well as preparation and application thereof
CN106450205A
Preparation method of artificial synaptic device based on Ti3C2-MXene / electrolyte structure
CN112103388A